The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s40471-015-0043-7
|View full text |Cite|
|
Sign up to set email alerts
|

A Review of the Health Benefits of Greenness

Abstract: Researchers are increasingly exploring how neighborhood greenness, or vegetation, may affect health behaviors and outcomes. Greenness may influence health by promoting physical activity and social contact; decreasing stress; and mitigating air pollution, noise, and heat exposure. Greenness is generally measured using satellite-based vegetation indices or land-use databases linked to participants’ addresses. In this review, we found fairly strong evidence for a positive association between greenness and physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
594
6
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 772 publications
(689 citation statements)
references
References 88 publications
20
594
6
14
Order By: Relevance
“…Numerous studies in multiple countries have demonstrated that recreational walking, increased physical activity and reduced sedentary time were associated with access to, and use of green space in working age adults, children and senior citizens (Epstein et al 2006;Kaczynski and Henderson 2007;Kaczynski et al 2008;Sugiyama and Ward Thompson 2008;Cochrane et al 2009;Almanza et al 2012;Lachowycz et al 2012;Astell-Burt et al 2013;Schipperijn et al 2013;Lachowycz and Jones 2014;Sugiyama et al 2014;Gardsjord et al 2014;James et al 2015;Sallis et al 2016). Almanza et al (2012) used satellite images and GPS and accelerometer data from children in several communities in California, the United States to demonstrate that increased residential greenness was positively associated with moderate to vigorous physical activity.…”
Section: Enhanced Physical Activity and Improved Fitnessmentioning
confidence: 99%
“…Numerous studies in multiple countries have demonstrated that recreational walking, increased physical activity and reduced sedentary time were associated with access to, and use of green space in working age adults, children and senior citizens (Epstein et al 2006;Kaczynski and Henderson 2007;Kaczynski et al 2008;Sugiyama and Ward Thompson 2008;Cochrane et al 2009;Almanza et al 2012;Lachowycz et al 2012;Astell-Burt et al 2013;Schipperijn et al 2013;Lachowycz and Jones 2014;Sugiyama et al 2014;Gardsjord et al 2014;James et al 2015;Sallis et al 2016). Almanza et al (2012) used satellite images and GPS and accelerometer data from children in several communities in California, the United States to demonstrate that increased residential greenness was positively associated with moderate to vigorous physical activity.…”
Section: Enhanced Physical Activity and Improved Fitnessmentioning
confidence: 99%
“…Many of the analyses in this review examined health outcomes for which multiple other reviews find consistent ties between greenness and physical health -namely physical activity, birth and developmental outcomes, and cardiovascular outcomes [1,7,[14][15][16]. The analyses in this review represent a relatively small sample of articles using a single analytic tool to estimate residential greenness.…”
Section: Discussionmentioning
confidence: 99%
“…Physical health outcomes were divided into 18 categories. These were adapted from categories identified in previous greenness and health literature reviews [1,7,8]. The manner of data collection for physical health outcomes was grouped into three categories, based on whether data were objective (i.e., biomarkers, vital signs), expert or clinician diagnoses (i.e., electronic medical records), or subjective (i.e., self-reported health questionnaires).…”
Section: Data Extractionmentioning
confidence: 99%
See 2 more Smart Citations